Digital transformation of work : Theorizing the process from an identity theory perspective - Zimmer, Markus P.; Gierlich-Joas, Maren (Elsevier BV, 2026)
Organizations increasingly engage in digital transformation (DT) of work. Previous research has shown that DT of work can engender intended and unintended consequences, such as tensions signaling organizational inertia. Scholars and practitioners often attribute transformation failure to such inertia. However, not inertia but the failure to evaluate and address it entails transformation failure. To evaluate inertia, we must dissect the nature of tensions signaling it. For this, we must understand how the DT of work process, from which they emerge, unfolds.
We theorize that DT of work unfolds from an interplay of DT work and function work. We empirically study this interplay through an ethnography of a large car manufacturer’s human resources function. We draw on identity theory—the concepts of identity claim and understanding—and illustrate that DT of work unfolds in three evolutionary periods marked by shifting identity claims and understandings reflected in DT work. We reveal that DT of work involves vertical (i.e., between claims and understandings) and horizontal (i.e., among coexisting understandings) identity tensions. Against previous literature’s contentions, these tensions indicate that DT of work shifts identity by addition, not substitution.
We contribute twofold. First, we conceptualize a process model of how DT of work unfolds from an identity theory perspective. This model outlines how revised identity claims initiate DT work and how DT of work produces multiple identity understandings entailing vertical and horizontal identity tensions. While vertical tensions trigger revisions of identity claims that initiate adjustments in DT work, horizontal tensions suggest DT of work shifts identity by addition. Second, we outline how our insights into identity tensions in DT of work can inform research into DT-induced identity tensions and underlying inertia.